Performance Measurement System and Business Performance Measurement System: A Comparative Study - Nor Mahirah, Mustapha; Sorooshian, Shahryar; Noor Azlinna, Azizan (IEOM Society International, 2016)
Many researchers claimed to use the term of a performance measurement system (PMS) to evaluate the business performance. However, these works have not adequately been classified in detail regarding the components they concentrate on,and what conditions are available in the empirical context they contemplate. This confusion is not pleasant because it affects the validity of new studies. This paper used a literature review as a methodology to address the issue of the differences between simple PMS and business performance measurement system (BPMS) and explain the proposed action should be taken to improve measurement system for SMEs in Malaysia. There are six main differences; goals, system and components, features, roles, process, and customer focus. Specifically, this paper clearly defined the significant to differentiate them. I argue that SMEs needs BPMS because SMEs are not a public agency or non-profit sector organizations as well as business activity is fundamental for SMEs. In conclusion, this paper sheds new light on the rarely acknowledged issue of BPMS with special attention to avoid the confusion between the two terms.